ID4 levels dictate the stem cell state in mouse spermatogonia - Helsel, Aileen R.; Yang, Qi-En; Oatley, Melissa; Lord, Tessa; Sablitzky, Fred; Oatley, Jon M. (Company of Biologists, 2017)
Spermatogenesis is a classic model of cycling cell lineages that depend on a balance between stem cell self-renewal for continuity and the formation of progenitors as the initial step in the production of differentiated cells. The mechanisms that guide the continuum of spermatogonial stem cell (SSC) to progenitor spermatogonial transition and precise identifiers of subtypes in the process are undefined. Here we used an Id4-eGfp reporter mouse to discover that EGFP intensity is predictive of the subsets, with the ID4-EGFPBright population being mostly, if not purely, SSCs, whereas the ID4-EGFPDim population is in transition to the progenitor state. These subsets are also distinguishable by transcriptome signatures. Moreover, using a conditional overexpression mouse model, we found that transition from the stem cell to the immediate progenitor state requires downregulation of Id4 coincident with a major change in the transcriptome. Collectively, our results demonstrate that the level of ID4 is predictive of stem cell or progenitor capacity in spermatogonia and dictates the interface of transition between the different functional states.